Global Proteomics Analysis of Bone Marrow: Establishing Talin-1 and Centrosomal Protein of 55 kDa as Potential Molecular Signatures for Myelodysplastic Syndromes - Moura, Arlindo A.; Bezerra, Maria Julia B.; Martins, Aline M. A.; Borges, Daniela P.; Oliveira, Roberta T. G.; Oliveira, Raphaela M.; Farias, Kaio M.; Viana, Arabela G.; Carvalho, Guilherme G. C.; Paier, Carlos R. K.; Sousa, Marcelo V.; Fontes, Wagner; et al. (Frontiers in Oncology, 2022)
Myelodysplastic syndrome (MDS) is a hematological disorder characterized by abnormal stem cell differentiation and a high risk of acute myeloid leukemia transformation. Treatment options for MDS are still limited, making the identification of molecular signatures for MDS progression a vital task. Thus, we evaluated the proteome of bone marrow plasma from patients (n = 28) diagnosed with MDS with ring sideroblasts (MDS-RS) and MDS with blasts in the bone marrow (MDS-EB) using label-free mass spectrometry. This strategy allowed the identification of 1,194 proteins in the bone marrow plasma samples. Polyubiquitin-C (UBC), moesin (MSN), and Talin-1 (TLN1) showed the highest abundances in MDS-EB, and centrosomal protein of 55 kDa (CEP55) showed the highest relative abundance in the bone marrow plasma of MDS-RS patients. In a follow-up, in the second phase of the study, expressions of UBC, MSN, TLN1, and CEP55 genes were evaluated in bone marrow mononuclear cells from 45 patients by using qPCR. This second cohort included only seven patients from the first study. CEP55, MSN, and UBC expressions were similar in mononuclear cells from MDS-RS and MDS-EB individuals. However, TLN1 gene expression was greater in mononuclear cells from MDS-RS (p = 0.049) as compared to MDS-EB patients. Irrespective of the MDS subtype, CEP55 expression was higher (p = 0.045) in MDS patients with abnormal karyotypes, while MSN, UBC, and TALIN1 transcripts were similar in MDS with normal vs. abnormal karyotypes. In conclusion, proteomic and gene expression approaches brought evidence of altered TLN1 and CEP55 expressions in cellular and non-cellular bone marrow compartments of patients with low-risk (MDS-RS) and high-risk (MDS-EB) MDSs and with normal vs. abnormal karyotypes. As MDS is characterized by disrupted apoptosis and chromosomal alterations, leading to mitotic slippage, TLN1 and CEP55 represent potential markers for MDS prognosis and/or targeted therapy.